Tendency for Recidivism Among Juvenile Offenders: A Case for Quality Assurance in the Correctional Programs of Nigerian Borstal Institutions - Ayorinde, Agbonna Samuel; Manafa , Fausta (International Journal of Educational Management, 2022)
The researchers find out tendencies for recidivism in the behaviours of juveniles offenders at Nigerian Borstal Training Institutions. From these they inferred the effectiveness of the correctional programs at the institutions. A total of 207 juveniles were purposively sampled and stratified across the institutions on the basis of their lengths of stay. A researcher-made questionnaire titled: Domains of Recidivism Assessment Questionnaire (DRAQ) was utilized to obtain data. The domains were basically aspects of misbehaviors. The Section B of DRAQ has 20 structured-item adapted from Hare’s Domains of Psychopathic Traits and Behaviour (DPTB). The instrument was face validated and a reliability coefficient of r=0.82 was derived through a test-re-test. Data were analyzed using percentages and t-test statistics. Scoring decisions were set at: less than 5 points (≤ 5) on DRAQ = Effective Correctional Program (ECP). A point (score) higher than 5 (≥ 5) but less from 29 (≤ 29) = Fairly Effective Correctional Program (FECP) and a point higher than 29 (≥ 29) = Ineffective Correctional Program (ICP) or high tendency for recidivism. Findings showed a reduction in tendency for recidivism in the juveniles as their length of stay increased. Specifically, while 51.7% of juveniles with short length of stay (i.e. less than one year) scored above 29 points on DRAQ only 12.1% of those with longer length of stay (i.e. above two years) scored above 29 points. Yet, this could not be interpreted to mean highly effective correctional programs as many of the juveniles across the lengths of stay still indicated some misbehavior (Domains of Recidivism). For example, despite varied period of exposure to correctional programs, 60% of them still indicated lack of self control, 58.7% indicated aimlessness or lacking direction; and 55.7% showed habit of not taking responsibility of wrongdoings. It was therefore recommended that the Borstal Institutions still have more to do to adjust juvenile behaviours.